(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
Polymerase Chain Reaction (PCR) is currently considered the gold-standard molecular method for detecting pathogenic nucleic acids in clinical specimens. Its exceptional sensitivity and specificity have enabled rapid diagnosis of a wide range of infectious diseases, ranging from classical bacterial infections to emerging viral pathogens. The recent COVID-19 pandemic demonstrated the enormous clinical and epidemiological significance of PCR-based diagnostics, as these methods allowed early detection, patient isolation, monitoring of viral load, and assessment of treatment efficacy. This article reviews the cellular and molecular principles of PCR, the varieties of PCR assays used in modern clinical microbiology, and the diagnostic importance of PCR for SARS-CoV-2—the causative agent of COVID-19. Additionally, the paper discusses limitations,